2017
DOI: 10.1177/2048872617730036
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous extracorporeal membrane oxygenation in electrical storm: five case reports addressing efficacy, transferring allowance or radiofrequency ablation support

Abstract: Extracorporeal membrane oxygenation systems have undergone rapid technological improvements and are now feasible options for medium-term support of severe cardiac or pulmonary failure. We report five cases of electrical storm that was rescued by the insertion of peripheral veno-arterial extracorporeal membrane oxygenation systems. This device could help to restore systemic circulation as well as permitting organ perfusion in patients with cardiogenic shock in relation to electrical storm thus achieving greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Patients with Brugada syndrome can suffer from ES, which causes excess catecholamine release from sympathetic fibers leading to sympathetic hyperactivity outflow to the heart resulting in potentially fatal arrhythmias. [3][4][5] Studies have shown benefits in restoring systemic circulation using ECMO in patients with cardiogenic shock related to ES and hemodynamic instability in ventricular arrhythmias. 4 ECMO support stabilizes the patient to facilitate future interventions in more favorable hemodynamic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with Brugada syndrome can suffer from ES, which causes excess catecholamine release from sympathetic fibers leading to sympathetic hyperactivity outflow to the heart resulting in potentially fatal arrhythmias. [3][4][5] Studies have shown benefits in restoring systemic circulation using ECMO in patients with cardiogenic shock related to ES and hemodynamic instability in ventricular arrhythmias. 4 ECMO support stabilizes the patient to facilitate future interventions in more favorable hemodynamic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Studies have shown benefits in restoring systemic circulation using ECMO in patients with cardiogenic shock related to ES and hemodynamic instability in ventricular arrhythmias. 4 ECMO support stabilizes the patient to facilitate future interventions in more favorable hemodynamic conditions. Due to the increase in mortality proportionally related to the length of time on ECMO, it is often used as a bridge to intervention rather than for prolonged survival in patients with cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Brugada Syndrome is an inherited cardiac electrical disorder occurring in the absence of obvious structural heart disease, leading to sudden cardiac death due to polymorphic ventricular tachycardia. Patients with Brugada Syndrome can suffer from electrical storms, which causes excess catecholamine release from sympathetic fibers leading to sympathetic hyperactivity outflow to the heart resulting in potentially fatal arrhythmias [3] [4] [5].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown benefit in restoring systemic circulation using ECMO in patients with cardiogenic shock related to ES and hemodynamic instability in ventricular arrhythmias [3]. ECMO support can stabilize the patient in order to facilitate future surgical interventions in more favorable hemodynamic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…18 In patients with cardiogenic shock due to an electrical storm percutaneous extracorporeal membrane oxygenation may result in hemodynamic stabilization with restoration of sufficient vital organ perfusion allowing invasive electophysiologic studies and therapies. 19 The management of electric storm is further discussed in an educational review. 20…”
mentioning
confidence: 99%